Efektivitas Perangkat Pembelajaran Fisika Berbasis Masalah Berbantuan Video untuk Meningkatkan Kemampuan Pemecahan Masalah Peserta Didik pada Materi Elastisitas - Susilawati Susilawati; Kosim Kosim; Fiki Rahmana (Postgraduate, University of Mataram, 2021)
This development research aims to produce an effective video-assisted problem-based physics learning tool to improve students' problem-solving skills on elasticity material. The research design used is a 4D model consisting of defining, designing, develop and disseminating. The products developed are syllabus, Lesson Plans, Student Worksheets, videos, and problem-solving ability questions. Data collection techniques using validation sheets and problem-solving ability questions. Product validity was assessed by six validators consisting of three expert validators and three practitioner validators. Furthermore, the effectiveness was obtained from a limited trial by providing problem-solving skills questions in the form of pretest and posttest which then the results were analyzed using N-Gain. The results showed that problem-solving abilities had increased with the average N-Gain test result being 0.61 in the medium category. Students show a positive response to online learning. So, it can be concluded that video-assisted problem-based physics learning tools are effective for improving students' problem-solving skills on elasticity materials during online learning